Research on the Present Situation and Countermeasures of Accounting Information Supervision of Listed Companies in China (Asian Business Research, 2022)
With the rapid expansion of the scale of China's capital market, the disclosure of accounting information of listedcompanies is not standardized and the problem of information transparency is becoming more and more prominent.This paper analyzes the present situation and existing problems of the accounting information supervision systemof listed companies in China from three aspects: the internal system supervision of listed companies, thesupervision of government legal system and the supervision of social intermediary system, and puts forward somecountermeasures for perfecting the supervision of accounting information of listed companies in China.